2010
DOI: 10.1002/aur.110
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution of autism in California: A retrospective birth cohort analysis

Abstract: Prenatal environmental exposures are among the risk factors being explored for associations with autism. We applied a new procedure combining multiple scan cluster detection tests to identify geographically defined areas of increased autism incidence. This procedure can serve as a first hypothesis-generating step aimed at localized environmental exposures, but would not be useful for assessing widely distributed exposures, such as household products, nor for exposures from non-point sources, such as traffic. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 24 publications
6
48
0
2
Order By: Relevance
“…A 2010 analysis of autism diagnoses in California 11 did not find that autism clustered preferentially around areas rich in IT industry. Instead, it found that clusters tended to occur in areas where parents were older and educated to a higher level than were parents in surrounding areas.…”
Section: Like Father Like Son?mentioning
confidence: 94%
“…A 2010 analysis of autism diagnoses in California 11 did not find that autism clustered preferentially around areas rich in IT industry. Instead, it found that clusters tended to occur in areas where parents were older and educated to a higher level than were parents in surrounding areas.…”
Section: Like Father Like Son?mentioning
confidence: 94%
“…The importance of SES emerged as a predictor of ASD risk in nine studies, 102,119,172,[240][241][242][243][244][245] but findings were mixed. Mainly in American studies, a higher SES, using proxies such as maternal income, occupation and education, was associated with ASD.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…102,244 Furthermore, spatial analysis of autism incidence in regions of California indicated a higher incidence that was independently characterized by higher levels of parental education. 245 …”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…Neuf études 102,119,172,[240][241][242][243][244][245] ont dégagé l'importance de la SSE comme prédicteur du risque de TSA, mais les constatations ont été mitigées. Des études, surtout améri-caines 172,[240][241][242] , ont établi un lien entre une meilleure SSE, mesurée par des substituts comme le revenu de la mère, sa profession et ses études, et le TSA.…”
Section: Situation Socioéconomiqueunclassified
“…ex., sous-diagnostic du TSA dans les familles dont la SSE est moins bonne) 102,244 . De plus, une analyse spatiale de l'incidence de l'autisme dans des régions de la Californie a révélé une incidence plus élevée, corrélée de manière indépendante aux études plus poussées faites par les parents 245 . .…”
Section: Situation Socioéconomiqueunclassified